2005
DOI: 10.1111/j.1365-2125.2005.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidneys contribute to the extrahepatic clearance of propofol in humans, but not lungs and brain

Abstract: AimsThe principal site for the metabolism of propofol is the liver. However, the total body clearance of propofol is greater than the generally accepted hepatic blood flow. In this study, we determined the elimination of propofol in the liver, lungs, brain and kidneys by measuring the arterial-venous blood concentration at steady state in patients undergoing cardiac surgery. MethodsAfter induction of anaesthesia, propofol was infused continuously during surgery. For measurement of propofol concentration, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 36 publications
(70 reference statements)
1
69
0
Order By: Relevance
“…Despite this potential importance, cutaneous drug metabolism is generally overlooked and rarely discussed during drug development. A better understanding of skin metabolism could also close the general in vitro-in vivo extrapolation gap for drugs where extensive extrahepatic metabolic clearance is suspected (Hiraoka et al, 2005;Gundert-Remy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this potential importance, cutaneous drug metabolism is generally overlooked and rarely discussed during drug development. A better understanding of skin metabolism could also close the general in vitro-in vivo extrapolation gap for drugs where extensive extrahepatic metabolic clearance is suspected (Hiraoka et al, 2005;Gundert-Remy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Siteeffect studies have confirmed that venous sampling is equally representative of arterial drug concentrations, provided the infusion interval prior to sampling is longer than 20 min. [39][40][41][42][43][44] Second, the mathematical model described in this study is inherently susceptible to changes in the anesthetic maneuver and is incapable of predicting propofol concentrations in routine clinical practice or beyond the infusion rates used in our study. In the absence of controls that omit propofol anesthesia, we are unable to attribute either the magnitude or the pattern of hemodynamic changes to the administration of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Contradicting reports exist in the literature over the potential propofol metabolism and/or sequestration in the lung (Dawidowicz et al, 2000;He et al, 2000;Hiraoka et al, 2005;Takizawa et al, 2005a). Reduction in propofol concentration across the lung in one study was proportional to the formation of the quinol metabolite and assessment of the blood concentration data suggested a lung extraction ratio of 0.40 (Dawidowicz et al, 2000).…”
Section: Applying a Pbpk Model To Predict Renal Metabolism 745mentioning
confidence: 99%